2022
DOI: 10.1002/wer.10751
|View full text |Cite
|
Sign up to set email alerts
|

Hospital wastewater treatment using eco‐friendly eugenol nanostructured lipid carriers: Formulation, optimization, and in vitro study for antibacterial and antioxidant properties

Abstract: In this study, nano‐formulation has been used to tackle one of the most important environmental problems which can be considered a major threat to human health. We prepared some eco‐friendly nanostructured lipid carriers (NLCs) as delivery agents to properly deliver an antibacterial agent (eugenol) into hospital wastewater in order to control bacterial growth. Eugenol‐loaded nanostructured lipid carriers were prepared by hot high‐speed homogenization. Then, the prepared nanocarriers were characterized using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Therefore, further studies are needed to evaluate the safety of eugenol for clinical use. Currently, several eugenol-related nanocapsules, including nanocoated, nanoparticle, and liposome formulations, have been extensively developed to improve the biocompatibility, stability, and bioactivity of eugenol ( 41 , 42 ). The development of eugenol nanopreparations will optimize its performance as an antibiotic adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are needed to evaluate the safety of eugenol for clinical use. Currently, several eugenol-related nanocapsules, including nanocoated, nanoparticle, and liposome formulations, have been extensively developed to improve the biocompatibility, stability, and bioactivity of eugenol ( 41 , 42 ). The development of eugenol nanopreparations will optimize its performance as an antibiotic adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms act as the indicators of water quality and determine the particular pathogens and their relative risk in wastewater (Shajari et al, 2022). For example, fecal Streptococci and Escherichia coli are the indicators of fecal contamination and bacteriophages for viral contamination (Eze et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In this direction, Mathur et al, 2022 performed battery of bioassays to check the efficiency of the treatment plants installed at various health care establishments. Likewise, Shajari et al, 2022 had prepared ecofriendly nanostructured lipid carriers (NLCs) to deliver antibacterial agent Eugenol to control bacterial growth in hospital wastewater. Such studies are an effort to monitor and provide safe recycled water.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of NLC-eugenol in sterile wastewater on wild bacteria strains revealed that 0.125 M was the most effective concentration to reduce bacterial quantities on wild S. aureus and Enterococcus faecalis strains (38% and 33.47%, respectively) at 37°C. At 25°C, NLC-eugenol at 0.125 M had the best impact, lowering total microbiological agents by 28.66% in hospital wastewater as shown in Table 1 [57].…”
Section: Nano-membranementioning
confidence: 96%